DIFFERENTIAL EXPRESSION AND RESPONSE OF GROWTH FACTORS IN DIFFERENT METASTATIC VARIANTS OF HUMAN PULMONARY GIANT CELL CARCINOMA - Zeng, Lingfang; Cui, Wen; Fang, Weigang; Zheng, Jie; Wu, Bingquang (Chinese Journal of Cancer Research, 2013)
The cell fines PGbE1 and PGLH7, which have high and low metastatic potential respectively, were two different variants isolated from human pulmonary giant cell carcinoma cell line PG. This study compared the expression and response of several growth factors TGFα TGFβ, bFGF, IL-6, IL-8 and ANG in the two cell lines. By using RT-PCR analysis and [3H] thymidine incorporation assay, it was found that IL-6,.TGFct and their receptors/L-6R and EGFR were expressed at higher level in PGbE1 cells than in PGLH7 cells, while no significant differences were found in the expression of ANG, bFGF, IL-8, IL-SR and TGFβ. Recombinant IL-6 and TGFα stimulated the proliferation of.both cells, while TGFβ had dual effects. These results suggest that ANG, bFGF IL-6, IL-8 and TGFαβ may be involved in the proliferation of pulmonary giant ceil carcinoma via autocrine mechanism, and IL-6 and TGFα may play an important role in the metastasis of tumor cells.